Доріс Лессінг - Шпиталь, А. (Слово і Час, 2009)
У статті розглянуто життєвий і творчий шлях відомої англійської письменниці, лауреатки Нобелівської
премії 2007 року з літератури. This article outlines the life and creative development of a famous English female writer Doris Lessing, the
winner of Nobel Prize for literature in 2007. В статье рассматривается жизненный и творческий путь
известной английской писательницы, лауреата Нобелевской
премии 2007 года по литературе.